Binding of a pancreatic nuclear protein is correlated with amylase enhancer activity. - Howard, G (1989)
The mouse amylase gene Amy-2.2 is expressed at high levels specifically in the acinar cells of the pancreas. The region between -172 and -110 of this gene includes sequence elements common to pancreas-specific genes. Nuclear proteins with specific affinity for this region were partially purified from rat pancreas. The consensus element of another pancreas-specific gene, elastase 1, competes for protein binding to the amylase sequences. Binding was localized by DNase I protection to the sequence -156 to -122. Site-directed mutagenesis of this sequence resulted in concomitant loss of protein binding and enhancer activity. Photo-affinity labelling of pancreatic nuclear extracts identified one predominant binding protein with a molecular weight of approximately 75 kDa. The data indicate that binding of this nuclear protein is essential for the enhancer activity of this pancreas-specific element.